Water-based two-component anti-erosion coating suitable for composite material photovoltaic frame and production process of water-based two-component anti-erosion coating

Through the use of aqueous two-component corrosion-resistant coatings, the problem of composite photovoltaic frames being susceptible to erosion in extreme environments is solved, forming a paint film with high thermal stability and high strength, extending service life and improving protective performance.

CN119286318APending Publication Date: 2025-01-10CHONGQING SANXIA PAINTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411621807.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Composite photovoltaic frames are susceptible to erosion in extreme environments, affecting their service life.

Method used

Use aqueous two-component corrosion-resistant coatings, including component A and component B. Component A consists of aqueous HDI curing agent, low viscosity HDI curing agent, aqueous IPDI curing agent and urethane-grade solvent. Component B is composed of fluoroolefins , vinyl ether copolymer, hydroxyl-containing aqueous resin and functional filler, the two are mixed in a ratio of 1:4-10 to form a paint film with high thermal stability and chemical inertness, and introduce high Mohs hardness silicon carbide powder and nano Alumina dispersion is used to enhance the strength of the paint film.

Benefits of technology

It effectively improves the wear resistance and protection performance of composite photovoltaic frames, extends the service life, and resists the erosion of environmental factors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286318A_ABST
    Figure CN119286318A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical engineering, in particular to a water-based bi-component anti-erosion coating suitable for a composite material photovoltaic frame and a production process. Fluoroolefin and vinyl ether copolymer serve as main film forming matter for film forming, fluorine atoms replace hydrogen atoms and surround a main chain to form a protective layer, so that a carbon chain is not prone to being invaded by the outside, and the corrosion resistance of the composite material photovoltaic frame is improved; a C-F bond in the coating is strong in bond energy, so that a paint film has excellent thermal stability and chemical inertness, the thickness of the construction paint film is low, and the influence of paint film abrasion on long-term protection is large, so that silicon carbide micro powder with high Mohs hardness is introduced and uniformly distributed in a system, and a more compact paint film is formed by matching with nano aluminum oxide dispersion liquid with high Mohs hardness; according to the method, the strength of a coating film is improved, so that the coating film can better resist abrasion when being in contact and friction with other substances, and the technical problem that in the prior art, when a composite material photovoltaic frame is applied, the composite material photovoltaic frame is extremely prone to being eroded by environmental factors, and then the service life is affected can be effectively solved through the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical engineering, and in particular to a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames and a production process. Background Art

[0002] In recent years, the photovoltaic power generation industry has developed rapidly worldwide, and the market size has continued to expand. The existing photovoltaic frames are mainly aluminum profile photovoltaic frames, and the penetration rate of composite material frames is low. However, compared with aluminum profile frames, composite material frames have more advantages: the cost of composite material frames is usually 20% to 25% lower than that of aluminum frames, which reduces the overall cost of photovoltaic modules; composite material frames have excellent weather resistance and can withstand harsh environments such as humidity, heat, acid, alkali and salt spray, and are particularly suitable for use in high humidity and corrosive environments; composite material frames have excellent insulation properties and do not require system grounding, which helps reduce the risk of potential induced degradation (PID) and improve power generation efficiency and system operation and maintenance safety.

[0003] However, composite photovoltaic frames are mostly used in open areas, harsh environments, such as outdoors, on tidal flats and offshore. These areas have extreme temperatures (alternating high and low temperatures), high humidity, strong ultraviolet radiation, high salt content, and rampant wind and sand. High temperature and ultraviolet rays accelerate the aging process of the frame material, causing surface brittleness and powdering; high humidity and high salinity will also reduce the mechanical properties of composite frames; the invasion of wind and sand will aggravate the wear on the frame surface and reduce the thickness of its effective protective layer.

[0004] In summary, composite photovoltaic frames are easily corroded by environmental factors during use, which in turn affects their service life. Summary of the invention

[0005] The purpose of the present invention is to provide a water-based two-component anti-corrosion coating and a production process suitable for composite photovoltaic frames, aiming to solve the technical problem in the prior art that composite photovoltaic frames are easily corroded by environmental factors during use, thereby affecting their service life.

[0006] To achieve the above-mentioned purpose, the present invention adopts a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, comprising component A and component B;

[0007] The component A comprises 20-70 kg of water-based HDI curing agent, 0-30 kg of low-viscosity HDI curing agent, 0-30 kg of water-based IPDI curing agent and 0-40 kg of urethane grade solvent;

[0008] The second component includes 10-60 kg of fluoroolefin and vinyl ether copolymer, 10-60 kg of hydroxyl-containing water-based resin, 0-5 kg ​​of cosolvent, 5-15 kg of auxiliary agent, 2-30 kg of pigment, 5-25 kg of functional filler and 8-15 kg of deionized water.

[0009] Wherein, the mixing ratio of the component A and the component B is component A: component B = 1: 4-10.

[0010] Wherein, the urethane-grade solvent includes one or a combination of 1-methoxy-2-propyl acetate and diacetate (1,2-propylene glycol).

[0011] The fluoroolefin and vinyl ether copolymer includes one or a combination of tetrafluoroethylene and vinyl ether copolymer and trifluoroethylene and vinyl ether copolymer.

[0012] Wherein, the co-solvent includes one or more combinations of ethylene glycol butyl ether, propylene glycol butyl ether, diethylene glycol butyl ether, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

[0013] The additives include various combinations of pH regulators, dispersants, defoamers, rheological additives, substrate wetting agents, leveling agents, ultraviolet light absorbers, adhesion promoters, wear-resistant additives, and matting additives.

[0014] The pigment includes one or more combinations of titanium dioxide, carbon black, highly weather-resistant organic red pigment, highly weather-resistant organic yellow pigment, and phthalocyanine blue.

[0015] The functional filler comprises one or more combinations of silicon carbide, nano-alumina dispersion, silicon micropowder, ceramic microbeads, sand powder, and nylon powder.

[0016] The present invention also provides a production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, which is used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as described above.

[0017] The steps include:

[0018] Step 1, prepare component A for standby use;

[0019] Step 2, prepare component B for standby use;

[0020] Step 3: Evenly mix the component A and the component B in a ratio of 1:4-10, and adjust the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

[0021] The specific method for preparing component A is as follows: taking water-based HDI curing agent, low-viscosity HDI curing agent, water-based IPDI curing agent and urethane-grade solvent in proportion, mixing them evenly, filtering and packaging after passing the inspection to obtain component A;

[0022] The specific method for preparing component B is as follows: deionized water and auxiliary agents are mixed in proportion, and then pigments and functional fillers are added, and dispersed with a sand mill to a fineness of ≤30 μm, and then fluoroolefin and vinyl ether copolymers, hydroxyl-containing water-based resins and auxiliary solvents are added in proportion, and auxiliary agents and functional fillers are added again, mixed evenly, and then filtered and packaged to obtain component B;

[0023] The total amount of the auxiliary agent added twice is 5-15 kg, and the total amount of the functional filler added twice is 5-25 kg.

[0024] The present invention discloses a water-based two-component anti-corrosion coating and production process suitable for composite photovoltaic frames. The water-based HDI curing agent, low-viscosity HDI curing agent, water-based IPDI curing agent and urethane-grade solvent are mixed in proportion, filtered and packaged after being inspected and qualified to obtain component A. Deionized water and auxiliary agents are mixed in proportion, pigments and functional fillers are added, and dispersed to a fineness of ≤30 μm by a sand mill. Fluoroolefin and vinyl ether copolymer, hydroxyl-containing water-based resin and auxiliary solvent are then added in proportion, and auxiliary agents and functional fillers are added again, mixed and filtered, packaged to obtain component B. The component A and the component B are mixed in a ratio of 1:4-10, and the construction viscosity is adjusted to obtain the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames.

[0025] The present invention uses fluoroolefin and vinyl ether copolymer as the main film-forming material, and fluorine atoms replace hydrogen atoms, surrounding the main chain to form a protective layer, so that the carbon chain is not easily attacked by the outside world. The CF bond in the coating has strong bond energy, so that the paint film has excellent thermal stability and chemical inertness. Compared with a simple acrylic system or a fluorine-containing acrylic system, it has more excellent performance.

[0026] Since the thickness of the paint film during construction is low, the wear of the paint film has a great impact on long-term protection. Therefore, silicon carbide micropowder with high Mohs hardness is introduced and evenly distributed in the system, and nano-alumina dispersion with high Mohs hardness is used to form a denser paint film, improve the strength of the coating film, and make the paint film better resist wear when in contact and friction with other substances.

[0027] This method can effectively solve the technical problem in the prior art that composite material photovoltaic frames are easily corroded by environmental factors during use, thereby affecting their service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 It is a flow chart of the steps of the production process of the water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames of the present invention. DETAILED DESCRIPTION

[0030] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0031] The present invention provides a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames, comprising component A and component B;

[0032] The component A comprises 20-70 kg of water-based HDI curing agent, 0-30 kg of low-viscosity HDI curing agent, 0-30 kg of water-based IPDI curing agent and 0-40 kg of urethane grade solvent;

[0033] The second component includes 10-60 kg of fluoroolefin and vinyl ether copolymer, 10-60 kg of hydroxyl-containing water-based resin, 0-5 kg ​​of cosolvent, 5-15 kg of auxiliary agent, 2-30 kg of pigment, 5-25 kg of functional filler and 8-15 kg of deionized water.

[0034] Wherein, the mixing ratio of the component A and the component B is component A: component B = 1: 4-10.

[0035] Wherein, the urethane-grade solvent includes one or a combination of 1-methoxy-2-propyl acetate and diacetate (1,2-propylene glycol).

[0036] The fluoroolefin and vinyl ether copolymer includes one or a combination of tetrafluoroethylene and vinyl ether copolymer and trifluoroethylene and vinyl ether copolymer.

[0037] Wherein, the co-solvent includes one or more combinations of ethylene glycol butyl ether, propylene glycol butyl ether, diethylene glycol butyl ether, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

[0038] The additives include various combinations of pH regulators, dispersants, defoamers, rheological additives, substrate wetting agents, leveling agents, ultraviolet light absorbers, adhesion promoters, wear-resistant additives, and matting additives.

[0039] The pigment includes one or more combinations of titanium dioxide, carbon black, highly weather-resistant organic red pigment, highly weather-resistant organic yellow pigment, and phthalocyanine blue.

[0040] The functional filler comprises one or more combinations of silicon carbide, nano-alumina dispersion, silicon micropowder, ceramic microbeads, sand powder, and nylon powder.

[0041] See also Figure 1 , Figure 1 It is a flow chart of the steps of the production process of the water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames of the present invention.

[0042] The present invention also provides a production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, which is used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as described above.

[0043] The steps include:

[0044] Step 1: Mix water-based HDI curing agent, low-viscosity HDI curing agent, water-based IPDI curing agent and urethane-grade solvent in proportion, filter and package to obtain component A after passing the inspection;

[0045] Step 2: Take deionized water and additives in proportion, mix them evenly, then add pigments and functional fillers, disperse them with a sand mill to a fineness of ≤30 μm, then add fluoroolefin and vinyl ether copolymers, hydroxyl-containing water-based resins and cosolvents in proportion, add additives and functional fillers again, mix them evenly, filter and package to obtain component B;

[0046] Step 3: Evenly mix the component A and the component B in a ratio of 1:4-10, and adjust the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

[0047] The total amount of the auxiliary agent added twice is 5-15 kg, and the total amount of the functional filler added twice is 5-25 kg.

[0048] Embodiment 1:

[0049] The present invention provides a production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, which is used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as described above.

[0050] The steps include:

[0051] S101, take 40kg of water-based HDI curing agent, 20kg of low-viscosity HDI curing agent, 20kg of water-based IPDI curing agent and 20kg of urethane grade solvent and mix them evenly, filter and package after passing the inspection, and obtain component A;

[0052] S102, take 10.4kg of ionized water, 0.1kg of pH regulator, 2kg of dispersant, 0.1kg of defoamer, 0.1kg of rheological additive and mix them evenly, add 3kg of carbon black and 7kg of silicon carbide powder, 3kg of aluminum oxide dispersion, disperse them with a sand mill to a fineness of ≤30μm, add 40kg of fluoroolefin and vinyl ether copolymer, 20kg of hydroxyl-containing water-based resin, 2kg of cosolvent, 0.6kg of substrate wetting agent, 0.6kg of leveling agent, 0.1kg of defoamer, 0.5kg of adhesion promoter, 3kg of wear-resistant additive, 0.5kg of rheological additive, 3kg of matting additive, 2kg of ultraviolet light absorber and 2kg of nylon powder and mix them evenly, filter and package them after passing the inspection to obtain component B;

[0053] S103, mixing the component A and the component B in a ratio of 1:5, and adjusting the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

[0054] Embodiment 2:

[0055] The present invention provides a production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, which is used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as described above.

[0056] The steps include:

[0057] S101, take 35kg of water-based HDI curing agent, 20kg of low-viscosity HDI curing agent, 10kg of water-based IPDI curing agent and 35kg of urethane grade solvent and mix them evenly, filter and package them after passing the inspection, and obtain component A;

[0058] S102, take 12kg of ionized water, 0.1kg of pH regulator, 2kg of dispersant, 0.1kg of defoamer, 0.1kg of rheological additive and mix them evenly, add 3kg of carbon black and 7kg of silicon carbide powder, 5kg of ceramic microbeads, disperse them with a sand mill to a fineness of ≤30μm, add 37kg of fluoroolefin and vinyl ether copolymer, 18kg of hydroxyl-containing water-based resin, 1.5kg of cosolvent, 0.7kg of substrate wetting agent, 0.7kg of leveling agent, 0.1kg of defoamer, 0.5kg of adhesion promoter, 4kg of wear-resistant additive, 0.4kg of rheological additive, 2kg of matting additive, 2kg of ultraviolet absorber, 3kg of nano-alumina dispersion and 0.8kg of deionized water and mix them evenly, filter and package them after passing the inspection to obtain component B;

[0059] S103, mixing the component A and the component B in a ratio of 1:4, and adjusting the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

[0060] Embodiment 3:

[0061] The present invention provides a production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, which is used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as described above.

[0062] The steps include:

[0063] S101, take 60kg of water-based HDI curing agent, 30kg of low-viscosity HDI curing agent and 10kg of water-based IPDI curing agent and mix them evenly, filter and package them after passing the inspection to obtain component A;

[0064] S102, take 9kg of ionized water, 0.1kg of pH regulator, 2kg of dispersant, 0.1kg of defoamer, and 0.1kg of rheological additive, mix them evenly, add 20kg of titanium dioxide and 5kg of silicon carbide powder, disperse them with a sand mill to a fineness of ≤30μm, add 45kg of fluoroolefin and vinyl ether copolymer, 5kg of hydroxyl-containing water-based resin, 3kg of cosolvent, 0.9kg of substrate wetting agent, 0.8kg of leveling agent, 0.1kg of defoamer, 0.6kg of adhesion promoter, 3kg of wear-resistant additive, 0.3kg of rheological additive, 1kg of matting additive, 1.5kg of ultraviolet light absorber and 2.5kg of nano-alumina dispersion, filter and package them after passing the inspection to obtain component B;

[0065] S103, mixing the component A and the component B in a ratio of 1:6, and adjusting the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

[0066] The water-based two-component anti-corrosion coating and production process suitable for composite photovoltaic frames of the present invention are used. The water-based two-component anti-corrosion coating and production process suitable for composite photovoltaic frames of the present invention are used. A water-based HDI curing agent, a low-viscosity HDI curing agent, a water-based IPDI curing agent and an urethane-grade solvent are mixed in proportion, and after passing the inspection, they are filtered and packaged to obtain component A. Deionized water and an auxiliary agent are mixed in proportion, and then pigments and functional fillers are added, and dispersed to a fineness of ≤30μm by a sand mill. Subsequently, fluoroolefin and vinyl ether copolymers, hydroxyl-containing water-based resins, auxiliary solvents and functional fillers are added in proportion, and the auxiliary agent is added again and mixed evenly, and then filtered and packaged to obtain component B. The component A and the component B are mixed evenly at a ratio of 1:4-10, and the construction viscosity is adjusted to obtain a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames;

[0067] The present invention uses fluoroolefin and vinyl ether copolymer as the main film-forming material, and fluorine atoms replace hydrogen atoms, surrounding the main chain to form a protective layer, so that the carbon chain is not easily attacked by the outside world. The CF bond in the coating has strong bond energy, so that the paint film has excellent thermal stability and chemical inertness. Compared with a simple acrylic system or a fluorine-containing acrylic system, it has more excellent performance.

[0068] Since the thickness of the paint film during construction is low, the wear of the paint film has a great impact on long-term protection. Therefore, silicon carbide micropowder with high Mohs hardness is introduced and evenly distributed in the system, and nano-alumina dispersion with high Mohs hardness is used to form a denser paint film, improve the strength of the coating film, and make the paint film better resist wear when in contact and friction with other substances.

[0069] This method can effectively solve the technical problem in the prior art that composite material photovoltaic frames are easily corroded by environmental factors during use, thereby affecting their service life.

[0070] The performance indicators of the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames of the present invention are as follows:

[0071]

[0072]

[0073] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, characterized in that: It includes component A and component B; The component A comprises 20-70 kg of water-based HDI curing agent, 0-30 kg of low-viscosity HDI curing agent, 0-30 kg of water-based IPDI curing agent and 0-40 kg of urethane grade solvent; The second component includes 10-60 kg of fluoroolefin and vinyl ether copolymer, 10-60 kg of hydroxyl-containing water-based resin, 0-5 kg ​​of cosolvent, 5-15 kg of auxiliary agent, 2-30 kg of pigment, 5-25 kg of functional filler and 8-15 kg of deionized water.

2. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 1, characterized in that: The mixing ratio of the component A and the component B is component A: component B = 1:4-10.

3. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 2, characterized in that: The urethane-grade solvent includes one or a combination of 1-methoxy-2-propyl acetate and (1,2-propylene glycol) diacetate.

4. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 3, characterized in that: The fluoroolefin and vinyl ether copolymer includes one or a combination of tetrafluoroethylene and vinyl ether copolymer and trifluoroethylene and vinyl ether copolymer.

5. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 4, characterized in that: The co-solvent includes one or more combinations of ethylene glycol butyl ether, propylene glycol butyl ether, diethylene glycol butyl ether, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

6. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 5, characterized in that: The additives include various combinations of pH regulators, dispersants, defoamers, rheological additives, substrate wetting agents, leveling agents, ultraviolet light absorbers, adhesion promoters, wear-resistant additives, and matting additives.

7. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 6, characterized in that: The pigment includes one or more combinations of titanium dioxide, carbon black, highly weather-resistant organic red pigment, highly weather-resistant organic yellow pigment, and phthalocyanine blue.

8. The water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 7, characterized in that: The functional filler comprises one or more combinations of silicon carbide, nano-alumina dispersion, silicon micropowder, ceramic microbeads, sand powder and nylon powder.

9. A production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames, used to produce the water-based two-component anti-corrosion coating suitable for composite photovoltaic frames as claimed in claim 8, characterized in that: The steps include: Step 1, prepare component A for standby use; Step 2, prepare component B for standby use; Step 3: Evenly mix the component A and the component B in a ratio of 1:4-10, and adjust the construction viscosity to obtain a water-based two-component anti-corrosion coating suitable for composite material photovoltaic frames.

10. The production process of a water-based two-component anti-corrosion coating suitable for composite photovoltaic frames according to claim 9, characterized in that: The specific method for preparing component A is: taking water-based HDI curing agent, low-viscosity HDI curing agent, water-based IPDI curing agent and urethane-grade solvent in proportion, mixing them evenly, filtering and packaging after passing the inspection to obtain component A; The specific method for preparing component B is as follows: deionized water and auxiliary agents are mixed in proportion, and then pigments and functional fillers are added, and dispersed with a sand mill to a fineness of ≤30 μm, and then fluoroolefin and vinyl ether copolymers, hydroxyl-containing water-based resins and auxiliary solvents are added in proportion, and auxiliary agents and functional fillers are added again, mixed evenly, and then filtered and packaged to obtain component B; The total amount of the auxiliary agent added twice is 5-15 kg, and the total amount of the functional filler added twice is 5-25 kg.

Citation Information

Patent Citations

  • Ink composition containing fluoro olefin-vinyl ether copolymer and photovoltaic component frame

    CN101921510A

  • High-weather-resistance FEVE water-based two-component fluorocarbon coating and production process

    CN117363184A

  • Waterborne coating for photovoltaic frame and preparation method of waterborne coating

    CN117586691A